Aktivitas Antioksidan Ekstrak Metanol Madu Cair dan Madu Bubuk Lokal Indonesia - La Ode Sumarlin; Achmad Tjachja; Riana Octavia; Nur Ernita (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2018)
Determination of antioxidant activity of methanol extract in local Indonesian liquid and powdered honey has been performed. The present study was intended to investigate the antioxidant activity and the phenolic, flavonoid, vitamin C content in methanol fraction of liquid and powdered honey. Powdered honey was produced using spray-drying technology with gum arabic as filler. Moreover, the levels of water, HMF and reducing sugar was also determined as the honey quality parameter. The result of the present research shows that powdered honey had antioxidant activity. Ekstrak Madu Kelengkeng Bubuk (EMKB) and Ekstrak Madu Rambutan Bubuk (EMRB) had antioxidant activity with IC50 values of 5621,62± 286,55 and 10293,88 ±14,04 mg/L, respectively. The antioxidant activity of Kelengkeng (EMKB) and Rambutan (EMRB) honey increased after the change to powder form 71.19% and 49,32 %, respectively. EMKB sample with the highest antioxidant activity has the highest total flavonoid content values (0,079±0,001 mg QE/g). The vitamin C content of the EMKB sample was 0.292 ± 0.000 mg/g, higher than the EMRB sample of 0.086 ± 0.005 mg/g. Powdered honey that produced had a decrease in water content values 50%. The water and hydroxymethyl furfural content of all sample comply with SNI 01-3545-2013, except the reducing sugar content.